Using wireless inertial measurement units for measuring hip range of motion through commonly used clinical tests - Oliva-Lozano, J. M.; Martín-Fuentes, I.; Muyor, J. M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
Hamstring extensibility is a crucial component of athletic performance and spinal health. In this regard, hip range of motion analysis through standardized clinical tests has been used as a valid and reliable method for measuring hamstring extensibility. Consequently, new inertial devices have been designed for this purpose. The aims of this study were to: (i) analyze the concurrent validity of inertial sensors for measuring hamstring extensibility through the Active Straight Leg Raise (ASLR) and Passive Straight Leg Raise (PSLR) tests; and (ii) analyze the test-retest reliability of inertial sensors for measuring hamstring extensibility through the ASLR and PSLR tests. A total of 18 healthy participants took part in this cross-sectional study. The hamstring extensibility was measured through the range of motion of the left and right hip in the Active Straight Leg Raise (ASLR) and Passive Straight Leg Raise (PSLR) tests. Data were collected by inertial sensors (WIMU Pro) and an ISOMED bi-level inclinometer, which was used as the reference instrument. The inertial sensors reported a standard error of the measurement (SEM) below 0.6° in all measurements. The R2 correlation and the intraclass correlation coefficient (ICC) were very close to 1 in all measurements. Regarding the reliability analysis, there were no significant differences (p > 0.05) between test and retest measures, and the SEM were below 0.8° in both instruments. The ICC were close to 1 in all cases as well. The coefficients of variation (CV) were below 2.7% in the inertial device and 2.2% in the inclinometer. This study showed that using microtechnology through WIMU Pro may be a valid and reliable method for measuring hip range of motion during the ASLR and PSLR tests.